Secondary battery
Patent Information
- Application Number
- CN202511658615.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-14
- Filing Date
- 2025-11-13
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-11-13
AI Technical Summary
因此,电阻在与隔膜弯曲部相连的电极外周部尤其变大,电极的电流密度不均容易增大
[0018]该结果是,能够提高二次电池的输出特性和循环特性。
Smart Images

Figure CN121709684B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a secondary battery. Background Technology
[0002] Patent Document 1 discloses a method for stacking positive and negative electrodes in a laminated secondary battery, sandwiching them between a fan-shaped folded strip separator. By using a fan-shaped separator to stack the electrodes, the step of cutting the separator is eliminated, improving the miniaturization of the manufacturing device and increasing productivity. In Patent Document 1, to prevent short circuits caused by electrodes getting caught in the separator due to thermal shrinkage, etc., an optimized distance between the electrode tip and the bent portion of the separator is proposed, with a certain distance set between them.
[0003] Furthermore, Patent Documents 2 and 3 disclose the use of gel polymer electrolytes, which are mixtures of non-aqueous electrolytes and polymers, as solid electrolytes for secondary batteries. When using gel polymer electrolytes as solid electrolytes for secondary batteries, safety can be improved by using the polymer to retain the electrolyte to prevent leakage and by using flame-retardant polymer materials. Patent Document 2 describes methods for controlling the viscosity of the gel polymer electrolyte. Patent Document 3 describes the inclusion of microcapsules, which will pre-form gelation initiators, in the electrolyte, and the release of the internal gelation initiator by applying heat or pressure to the microcapsules after injection of the electrolyte.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent No. 7448357.
[0007] Patent Document 2: Japanese Patent No. 6159199.
[0008] Patent document 3: Japanese Patent No. 6279241.
[0009] The technical problem that the invention aims to solve
[0010] When using gel polymer electrolytes in laminated secondary batteries, an electrode and separator laminate is inserted into an outer casing, and electrolyte material is injected. After vacuum sealing the outer casing, the electrolyte material is gelled. During vacuum sealing, the laminate is subjected to constraint pressure from the outer casing, and the electrolyte material is squeezed out towards the outer periphery of the electrode, thus the amount of electrolyte material at the outer periphery of the electrode tends to increase.
[0011] During the heating process used to gel the electrolyte material, the heat generation is greater at the outer periphery of the electrode, making gelation easier and increasing viscosity compared to the center. High-viscosity gels hinder ion transport, resulting in a higher ion transport resistance at the outer periphery than at the center, leading to uneven current density during charging and discharging. This uneven current density causes a decrease in the output characteristics of the secondary battery, localized degradation of the active material, and consequently, reduced cycle performance.
[0012] In the laminated secondary battery of Patent Document 1, a U-shaped bend in the separator is provided at a position away from the electrode end, forming a space surrounded by the electrode end and the bend in the separator. Therefore, when a gel polymer electrolyte is used in the laminated secondary battery of Patent Document 1, the electrolyte material is held in the space between the electrode end and the bend in the separator, and the high-viscosity gel polymer electrolyte tends to accumulate. Therefore, when the separator thermally shrinks, the high-viscosity gel polymer electrolyte is pressed from the bend in the separator into the outer periphery of the electrode. As a result, the resistance becomes particularly large at the outer periphery of the electrode connected to the bend in the separator, and the uneven current density of the electrode tends to increase.
[0013] When the gel polymer electrolyte of Patent Document 2 is used in a laminated secondary battery, the low viscosity electrolyte is easily squeezed to the outer periphery of the electrode due to the constraint pressure of the outer casing, making it difficult to eliminate the uneven current density of the electrode.
[0014] When the gel polymer electrolyte of Patent Document 3 is used in a laminated secondary battery, the microcapsules are easily squeezed to the outer periphery of the electrode due to the constraint pressure of the outer casing, making it difficult to eliminate uneven current density of the electrode. Even if the microcapsules are pre-positioned locally on the electrode, local placement is difficult to achieve because they are carried away by the flow of the electrolyte during injection. Summary of the Invention
[0015] In view of the above problems, the object of the present invention is to improve the output characteristics and cycle characteristics in a laminated secondary battery using a gel polymer electrolyte.
[0016] To achieve the above objectives, in one embodiment of this disclosure, an electrode, a membrane, an ion-conducting gel polymer electrolyte, and an outer casing housing the electrode, the membrane, and the gel polymer electrolyte are included. The electrode has a positive electrode containing a positive active material and a negative electrode containing a negative active material. The positive and negative electrodes are alternately stacked with the membrane in between. The membrane has a first portion that holds at least one of the positive and negative electrodes and a second portion that bends the first portions of the stacked membranes to connect to each other. The electrode has a bent-side outer periphery including a bent-side end located opposite the second portion of the membrane. The bent-side outer periphery of at least one of the positive or negative electrodes contains an inorganic solid electrolyte.
[0017] This improves the ionic conductivity of the outer periphery of the curved side where the resistance tends to increase due to the high viscosity of the gel polymer electrolyte, and reduces the unevenness of the current density of the electrode.
[0018] This result demonstrates the ability to improve the output and cycle characteristics of secondary batteries. Attached Figure Description
[0019] Figure 1 This is a cross-sectional view of the secondary battery according to the first embodiment.
[0020] Figure 2 It is a cross-sectional view showing a portion of a stacked array of electrodes.
[0021] Figure 3 This is a top view of the electrodes.
[0022] Figure 4 It is a diagram showing the morphology of a positive or negative electrode material mixed with an inorganic solid electrolyte.
[0023] Figure 5 It is a diagram showing the morphology of the surface of the positive or negative electrode material covered by an inorganic solid electrolyte.
[0024] Figure 6 This is a diagram showing the morphology of an inorganic solid electrolyte covering the surface of a membrane.
[0025] Figure 7 This is a flowchart illustrating the manufacturing process of a secondary battery.
[0026] Figure 8 It is a diagram used to illustrate the manufacturing process of the positive and negative electrodes.
[0027] Figure 9 This is a graph showing the output and loop characteristics of the embodiments and comparative examples. Detailed Implementation
[0028] Hereinafter, various methods for implementing this disclosure are described with reference to the accompanying drawings. In each method, the same reference numerals are sometimes given to parts corresponding to matters described in the preceding methods, and repeated descriptions are omitted. Where only a part of the structure is described in each method, other methods previously described can be applied to the other parts of the structure. Not only can the parts that are explicitly shown to be able to be specifically combined be combined with each other, but embodiments can also be partially combined with each other even if not explicitly shown, as long as the combination does not particularly create an obstacle.
[0029] (First Implementation)
[0030] Hereinafter, a first embodiment of the present disclosure will be described based on the accompanying drawings. The secondary battery 1 of this embodiment is a lithium-ion battery in which lithium ions are used as conductive ions for conduction.
[0031] like Figure 1 As shown, the secondary battery 1 of this embodiment includes a positive electrode 10, a negative electrode 20, a separator 30, and an outer casing 50. Hereinafter, the positive electrode 10 and the negative electrode 20 will also be referred to as electrodes 10 and 20.
[0032] The secondary battery 1 of this embodiment is configured as a laminated secondary battery in which a laminate 40 of electrodes 10, 20 and separator 30 is encapsulated in an outer casing 50. The laminate 40 of electrodes 10, 20 and separator 30 and gel polymer electrolyte 60 together constitute a battery cell.
[0033] Electrodes 10 and 20 are formed into flat, plate-like components. Multiple positive electrodes 10 and multiple negative electrodes 20 are provided, and the number of positive electrodes 10 and negative electrodes 20 can be arbitrarily set. Figure 1 This represents an example where two layers of each electrode are stacked, one for positive electrode 10 and one for negative electrode 20.
[0034] The diaphragm 30 is formed from a porous material such as a resin-based porous membrane, woven fabric, or nonwoven fabric. Materials for the diaphragm 30 can include, for example, polyolefin resins such as polypropylene and polyethylene, and nonwoven fabrics such as cellulose, aramid, and polyester.
[0035] The diaphragm 30 can also be surface-coated with a dissimilar material. Examples of dissimilar materials include mixtures of ceramic materials such as alumina, titanium dioxide, boehmite, magnesium hydroxide, and barium sulfate with binders such as PVDF, PTFE, acrylic copolymers, and PVA, or mixtures of resin materials such as meta-aramid and para-aramid with the aforementioned binders.
[0036] In this embodiment, the diaphragm 30 is configured as a strip-shaped component. The strip-shaped diaphragm 30 is formed in a fan-shaped fold, having multiple flat portions 30a and multiple curved portions 30b. Hereinafter, the flat portions 30a of the diaphragm 30 will be referred to as diaphragm flat portions 30a, and the curved portions 30b of the diaphragm 30 will be referred to as diaphragm curved portions 30b. Furthermore, the flat portions 30a are the first part of the diaphragm 30, and the curved portions 30b are the second part of the diaphragm 30.
[0037] The flat portion 30a and the curved portion 30b of the diaphragm are formed continuously. Adjacent flat portions 30a are connected by the curved portion 30b.
[0038] Multiple diaphragm flat portions 30a are arranged in parallel. A positive electrode 10 and a negative electrode 20 are alternately arranged between adjacent diaphragm flat portions 30a. The positive electrode 10 and the negative electrode 20 are respectively held by the diaphragm flat portions 30a, and the diaphragm flat portions 30a are held by the positive electrode 10 and the negative electrode 20. The diaphragm flat portions 30a hold at least one of the electrodes of the positive electrode 10 and the negative electrode 20.
[0039] The diaphragm bend 30b is formed by bending the diaphragm 30 to the outer side of the ends of the electrodes 10 and 20, which are plate-shaped members. The diaphragm bend 30b is bent in such a way that the stacked diaphragm flat portions 30a are connected to each other. The diaphragm bend 30b is arranged such that a predetermined distance is provided between it and the ends of the electrodes 10 and 20. Therefore, a gap is formed between the diaphragm bend 30b and the ends of the electrodes 10 and 20.
[0040] The outer casing 50 is composed of two laminated films 51 and 52. The outer periphery of the two laminated films 51 and 52 are joined together to form a receiving space inside. The laminated films 51 and 52 are configured, for example, to laminate resin layers and aluminum foil on both sides. The receiving space of the outer casing 50 houses a laminate 40 of electrodes 10 and 20 and a diaphragm 30.
[0041] Inside the outer casing 50, a gel polymer electrolyte 60 with ionic conductivity is housed together with the laminate 40 of electrodes 10, 20 and diaphragm 30. The gel polymer electrolyte 60 is distributed from the positive electrode 10 to the negative electrode 20, sandwiched between the diaphragm 30, and is arranged in a manner that permeates the interior of both the positive electrode 10 and the negative electrode 20. The gel polymer electrolyte 60 is a mixture of a polymeric compound with gelling properties and a non-aqueous electrolyte, or a polymeric compound with both ionic conductivity and gelling properties. The gel polymer electrolyte 60 is a polymeric compound that retains the non-aqueous electrolyte, possesses moderate plasticity and adhesiveness, and has ionic conductivity close to that of a non-aqueous electrolyte. The gel polymer electrolyte 60, composed of polymeric compounds with both ionic conductivity and gelling properties, exhibits ionic conductivity even without the presence of a non-aqueous electrolyte, except that the electrolyte constituent materials are composed of monomers and electrolyte salts. It also possesses the same plasticity and adhesiveness as gel polymer electrolytes containing a non-aqueous electrolyte.
[0042] Electrolyte constituent materials, which serve as raw materials for gel polymer electrolyte 60, are injected into an outer casing 50 and sealed inside the outer casing 50. The electrolyte constituent materials then polymerize within the outer casing 50, thereby gelling and yielding gel polymer electrolyte 60. The electrolyte constituent materials comprise a non-aqueous electrolyte and monomers that are raw materials for a polymer compound with gelling properties. A polymerization initiator can be added to the electrolyte constituent materials beforehand, and the monomers contained in the electrolyte constituent materials can be polymerized by heating at a specified temperature.
[0043] By pre-filling the outer casing 50 with the electrolyte constituent material, the electrolyte constituent material permeates the interior of the electrodes 10 and 20. In this state, the electrolyte constituent material is polymerized to form a gel polymer electrolyte 60. As a result, the electrolyte can be maintained inside the positive electrode 10 and the negative electrode 20 at all times, enabling smooth charge and discharge reactions.
[0044] Examples of polymeric compounds with gelling properties include fluoropolymers containing vinylidene fluoride units, acrylic resins containing (meth)acrylic acid and / or (meth)acrylate units, and polyether resins containing polyalkylene oxide units. Examples of fluoropolymers containing vinylidene fluoride units include polyvinylidene fluoride, copolymers containing vinylidene fluoride units and hexafluoropropylene units, and copolymers containing vinylidene fluoride units and trifluoroethylene units. Polymeric compounds that combine ionic conductivity and gelling properties (e.g., compounds with alkylene oxide structures) such as polyethylene oxide, polyethylene carbonate, polysuccinate, polyphenylene sulfide, polyethyleneimine, and poly(1,3-dioxolane) can also be used.
[0045] Non-aqueous electrolytes contain lithium salts and solvents for dissolving them. LiPF6, LiBF4, LiClO4, Li(FSO2)2N, Li(CF3SO2)(FSO2)N, Li(CF3SO2)2N, LiC(CF3SO2)3, LiBF2(C2O4), LiB(C2O4)2, etc., can be used as lithium salts. A single lithium salt can be used, or two or more can be used in combination.
[0046] As a solvent, one or more mixtures of organic solvents such as cyclic carbonates such as ethylene carbonate, propylene carbonate, vinylene carbonate, and butyl carbonate, or chain carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and dipropyl carbonate (DPC) can be used. Furthermore, ionic liquids containing ammonium salts, imidazolium salts, sulfonium salts, piperidinium salts, pyridinium salts, pyrrolidineium salts, phosphonium salts, and morpholinium salts can also be used as solvents.
[0047] As polymerization initiators, in the case of free radical polymerization, for example, 2,2'-azobisbutyronitrile and benzoyl peroxide can be used; in the case of cationic polymerization, for example, benzenesulfonate esters and alkyl sulfonate salts can be used. Furthermore, the polymerization initiator can also be anion of the electrolyte salt constituting the non-aqueous electrolyte, or hydrofluoric acid as a byproduct.
[0048] Next, use Figure 2 , Figure 3 The positive electrode 10 and the negative electrode 20 will be explained. Figure 2 This is a cross-sectional view of the positive electrode 10 and the negative electrode 20. Figure 3 This is a top view of positive electrode 10 and negative electrode 20.
[0049] like Figure 3 As shown, the positive electrode 10 and the negative electrode 20 are roughly rectangular plate-shaped components. Figure 2 , Figure 3As shown, the positive electrode 10 has three regions: a first positive electrode outer peripheral portion 10a, a second positive electrode outer peripheral portion 10b, and a positive electrode center portion 10c. The first positive electrode outer peripheral portion 10a, the second positive electrode outer peripheral portion 10b, and the positive electrode center portion 10c are arranged in a direction connecting the first positive electrode end portion 10d on the side near the diaphragm bend portion 30b and the second positive electrode end portion 10e on the side away from the diaphragm bend portion 30b. The direction connecting the first positive electrode end portion 10d and the second positive electrode end portion 10e is orthogonal to the direction in which the positive electrode 10 and the negative electrode 20 are stacked, and the direction intersecting the diaphragm bend portion 30b is defined as... Figure 2 , Figure 3 The left and right directions in the middle.
[0050] The outer periphery 10a of the first positive electrode is the region in the positive electrode 10 that includes the first positive terminal portion 10d. The outer periphery 10a of the first positive electrode is the region in the positive electrode 10 that includes the first positive terminal portion 10d and has a length of less than 1 / 3 of the length of the positive electrode 10 in the direction connecting the first positive terminal portion 10d and the second positive terminal portion 10e.
[0051] The outer periphery 10b of the second positive electrode is the region in the positive electrode 10 that includes the second positive terminal portion 10e. The outer periphery 10b of the second positive electrode is the region in the positive electrode 10 that includes the second positive terminal portion 10e and has a length of less than 1 / 3 of the positive electrode 10 in the direction connecting the first positive terminal portion 10d and the second positive terminal portion 10e.
[0052] The positive electrode center portion 10c is the region located in the center of the positive electrode 10 in the direction connecting the first positive electrode portion 10d and the second positive electrode portion 10e, and is the region sandwiched between the first positive electrode outer peripheral portion 10a and the second positive electrode outer peripheral portion 10b.
[0053] The negative electrode 20 has three regions: a first negative electrode outer periphery 20a, a second negative electrode outer periphery 20b, and a negative electrode center portion 20c. The first negative electrode outer periphery 20a, the second negative electrode outer periphery 20b, and the negative electrode center portion 20c are arranged in a direction connecting the first negative electrode portion 20d on the side near the diaphragm bend 30b and the second negative electrode portion 20e on the side away from the diaphragm bend 30b. The direction connecting the first negative electrode portion 20d and the second negative electrode portion 20e is the same as the direction connecting the first positive electrode portion 10d and the second positive electrode portion 10e described above.
[0054] The first negative electrode outer periphery 20a is the region in the negative electrode 20 that includes the first negative electrode end portion 20d. The first negative electrode outer periphery 20a is the region in the negative electrode 20 that includes the first negative electrode end portion 20d and has a length of less than 1 / 3 of the negative electrode 20 in the direction connecting the first negative electrode end portion 20d and the second negative electrode end portion 20e.
[0055] The second negative electrode outer periphery 20b is the region in the negative electrode 20 that includes the second negative electrode portion 20e. The second negative electrode outer periphery 20b is the region in the negative electrode 20 that includes the second negative electrode portion 20e and has a length of less than 1 / 3 of the negative electrode 20 in the direction connecting the first negative electrode portion 20d and the second negative electrode portion 20e.
[0056] The negative electrode center portion 20c is the region located in the center of the negative electrode 20 in the direction connecting the first negative electrode end portion 20d and the second negative electrode end portion 20e, and is the region sandwiched between the first negative electrode outer peripheral portion 20a and the second negative electrode outer peripheral portion 20b.
[0057] The outer peripheral portions 10a and 20a of the first positive electrode are curved outer peripheral portions. The outer peripheral portions 10b and 20b of the second positive electrode are opposite outer peripheral portions. The central portion 10c of the positive electrode and 20c of the negative electrode are central portions. The first positive terminal portion 10d and 20d of the first negative terminal portion are curved end portions. The second positive terminal portion 10e and 20e of the second negative terminal portion are opposite end portions.
[0058] As described above in the "Technical Problem to be Solved by the Invention," the viscosity of the gel polymer electrolyte 60 increases in the outer periphery portions 10a and 10b of the positive electrode and 20a and 20b of the negative electrode, making it prone to increasing ion transport resistance. In particular, in the first outer periphery portion 10a of the positive electrode and the first outer periphery portion 20a of the negative electrode near the membrane bend 30b, the resistance tends to increase along with the increase in the viscosity of the gel polymer electrolyte 60.
[0059] The positive electrode 10 includes a positive current collector 11 and a positive electrode material 12. Layers of the positive electrode material 12 are formed on both sides of the positive current collector 11. The negative electrode 20 includes a negative current collector 21 and a negative electrode material 22. Layers of the negative electrode material 22 are formed on both sides of the negative current collector 21.
[0060] A positive terminal 11a is formed in the positive current collector 11. No positive electrode material 12 is provided in the positive terminal 11a. A negative terminal 21a is formed in the negative current collector 21. No negative electrode material 22 is provided in the negative terminal 21a.
[0061] The positive current collector 11 can be made of materials such as aluminum, stainless steel, nickel, titanium, or alloys thereof. The negative current collector 21 can be made of materials such as copper, stainless steel, nickel, titanium, or alloys thereof.
[0062] The positive electrode material 12 comprises a positive electrode active material 13 and an inorganic solid electrolyte 70. In the first positive electrode peripheral portion 10a, the positive electrode material 12 comprises the positive electrode active material 13 and the inorganic solid electrolyte 70. In the second positive electrode peripheral portion 10b and the positive electrode center portion 10c, the positive electrode material 12 comprises the positive electrode active material 13 but does not contain the inorganic solid electrolyte 70. That is, the presence or absence of the inorganic solid electrolyte 70, or the content of the inorganic solid electrolyte 70, differs in the first positive electrode peripheral portion 10a, the second positive electrode peripheral portion 10b, and the positive electrode center portion 10c. The thickness of the positive electrode material 12 is preferably 0.02 mm or more and 0.2 mm or less, more preferably 0.04 mm or more and 0.1 mm or less.
[0063] The negative electrode material 22 comprises a negative electrode active material 23 and an inorganic solid electrolyte 70. In the outer peripheral portion 20a of the first negative electrode, the negative electrode material 22 comprises the negative electrode active material 23 and the inorganic solid electrolyte 70. In the outer peripheral portion 20b and the central portion 20c of the negative electrode, the negative electrode material 22 comprises the negative electrode active material 23 but does not contain the inorganic solid electrolyte 70. That is, the presence or absence of the inorganic solid electrolyte 70, or the content of the inorganic solid electrolyte 70, differs in the first outer peripheral portion 20a, the second outer peripheral portion 20b, and the central portion 20c. The thickness of the negative electrode material 22 is preferably 0.02 mm or more and 0.15 mm or less, more preferably 0.03 mm or more and 0.8 mm or less.
[0064] In the positive electrode 10, the inorganic solid electrolyte 70 can be disposed in the positive electrode material 12 in any form. Similarly, in the negative electrode 20, the inorganic solid electrolyte 70 can be disposed in the negative electrode material 22 in any form.
[0065] For example, such as Figure 4 As shown, the inorganic solid electrolyte 70 can be dispersed together with the positive electrode active material 13 in the positive electrode material 12, or the inorganic solid electrolyte 70 can be dispersed together with the negative electrode active material 23 in the negative electrode material 22. Furthermore, as... Figure 5 As shown, the inorganic solid electrolyte 70 can be configured to cover the surface of the positive electrode active material 13, or it can be configured to cover the surface of the negative electrode active material 23. Furthermore, as... Figure 6 As shown, the inorganic solid electrolyte 70 can be configured to cover the surface of the positive electrode 10 side of the diaphragm 30, or the inorganic solid electrolyte 70 can be configured to cover the surface of the negative electrode 20 side of the diaphragm 30.
[0066] The inorganic solid electrolyte 70 exhibits ionic conductivity. In the positive electrode 10, the outer periphery 10a of the first positive electrode, which has a higher resistance, contains the inorganic solid electrolyte 70, thereby improving the ionic conductivity of the outer periphery 10a. As a result, the current density unevenness of the positive electrode 10 can be reduced. Similarly, in the negative electrode 20, the outer periphery 20a of the first negative electrode, which has a higher resistance, contains the inorganic solid electrolyte 70, thereby improving the ionic conductivity of the outer periphery 20a. As a result, the current density unevenness of the negative electrode 20 can be reduced.
[0067] As the positive electrode active material 13, any material suitable for lithium-ion batteries can be used. For example, layered rock salt type active materials, olivine type active materials, and spinel type active materials can be used as the positive electrode active material 13. For example, LiNi can be used as a layered rock salt type active material. x Co y Mn z O2 (NCM), LiNi x Co y Al z Ternary cathode materials such as O2 (NCA) can be used. As olivine-type active materials, LiFePO4 (LFP) and LiMn can be employed. 1- x Fe x LiMnPO4 (LMFP), LiMnPO4 (LMP), LiCoPO4 (LCP), and LiNiPO4 (LNP) are used as spinel-type active materials. For example, LiMn2O4 (LMO) and LiNiPO4 can also be used. 0.5 Mn 1.5 O4 (LNMO).
[0068] As the negative electrode active material 23, any material suitable for use in lithium-ion batteries can be used. For example, carbon-based negative electrode materials such as graphite, amorphous carbon, fullerene, and carbon nanotubes, lithium metal materials, metal-based negative electrode materials such as silicon and tin, oxide-based negative electrodes such as Nb2O5 and TiO2, or composite materials thereof can be used as the negative electrode active material 23.
[0069] As the inorganic solid electrolyte 70 added to the positive electrode material 12 and the negative electrode material 22, for example, a sulfide-based solid electrolyte or an oxide-based solid electrolyte can be used. As a sulfide-based solid electrolyte, for example, a sulfide-germanium ore type solid electrolyte can be used. As an oxide-based solid electrolyte, for example, a garnet-type solid electrolyte, a NASICON-type solid electrolyte, a LISICON-type solid electrolyte, or a pyrochlore-type solid electrolyte can be used. Pyrochlore-type solid electrolytes will be described in detail later.
[0070] Li6PS5Cl can be used as a sulfide-germanium ore type solid electrolyte, for example. Li7La3Zr2O can be used as a garnet type solid electrolyte, for example. 12 (LLZ). As a NASICON-type solid electrolyte, for example, Li can be used. 1.4 Al 0.4 Ti 1.6 (PO4)3 (LATP). As a LISICON-type solid electrolyte, for example, Li can be used. 2+2x Zn 1-x GeO4. As a pyrochlore-type solid electrolyte, Li can be used, for example. 1.25 La 0.58 Nb₂O₆F(LLNOF), Li 1.25 La 0.58 Ta₂O₆F (LLTOF). Compared to sulfide-based solid electrolytes, oxide-based solid electrolytes can suppress partial decomposition caused by reaction with gel polymer electrolyte 60. Therefore, oxide-based solid electrolytes are preferred as inorganic solid electrolyte 70.
[0071] The content of inorganic solid electrolyte 70 in the positive electrode 10 and the negative electrode 20 can be the same or different. Preferably, the content of inorganic solid electrolyte 70 in the positive electrode 10 and the negative electrode 20 is greater than that in the negative electrode 20. Compared with the negative electrode 20, the interfacial resistance between the electrode and the electrolyte of the positive electrode 10 is larger. Therefore, by making the content of inorganic solid electrolyte 70 in the positive electrode 10 greater than that in the negative electrode 20, the ionic conductivity of the positive electrode 10 can be increased, and the current density unevenness can be reduced more effectively.
[0072] Next, the pyrochlore-type solid electrolyte used as the inorganic solid electrolyte 70 will be described. The pyrochlore-type solid electrolyte of this embodiment has a compositional formula consisting of "Aa". 2-α Ab (1+α) / 3 B2O 7-β X γ The structure of pyrochlore is represented by the symbol "". In the above formula, O is an oxygen atom, and Aa, Ab, B, and X represent any element or group. Aa, Ab, and B are different types of cations, and O and X are different types of anions. Aa is an alkali metal cation. Pyrochlore-type solid electrolytes contain multiple cations composed of alkali metal cation Aa and multiple cations Ab and B other than alkali metal cation Aa. That is, pyrochlore-type solid electrolytes contain multiple cations including alkali metal cation Aa in their composition.
[0073] Pyrochlore-type solid electrolytes possess a crystalline structure forming a three-dimensional octahedral network of BO6. BO6 is centered on cation B, with O located at the vertices, sharing vertices with adjacent BO6 ions. Within this three-dimensional network of BO6, hexagonal channel structures are formed, each containing cation A and anion X.
[0074] In the above composition formula, 0.6 < α < 2.0, 0 < β ≤ 1, and 0 < γ ≤ 1. The composition ratio of Aa and Ab changes with changes in α, and the composition ratio of O and X changes with changes in β and γ.
[0075] The cation Aa is an alkali metal cation. The alkali metal represented by Aa can be any one of Li, Na, K, Rb, and Cs. Mg or H, other than alkali metals, can also be used as the cation Aa. That is, the cation Aa contains at least one selected from Li, Na, K, Rb, Cs, Mg, and H. In this embodiment, Li is used as Aa. The composition ratio (2-α) of Aa is in the range of 0 < (2-α) < 1.4.
[0076] The cation Ab contains at least a lanthanide element. As the lanthanide element represented by Ab, at least one of La, Ce, Nd, and Sm can be used. In this embodiment, La is used as Ab. The composition ratio of Ab (1+α) / 3 is in the range of 0.53 < (1+α) / 3 < 1.
[0077] The basic structure of cationic Ab is composed of lanthanides, and some of the lanthanides constituting Ab can be replaced by alkaline earth metals (Ca, Mg, Sr, etc.). The pyrochlore-type solid electrolyte of this embodiment is considered to have improved ionic conductivity because it contains lanthanides in its crystal structure, resulting in defects in the crystal structure of the pyrochlore structure with the above-mentioned composition formula 0.6 < α < 2.0, 0 < β ≤ 1. In this embodiment, La is used as Ab.
[0078] In the pyrochlore-type solid electrolyte of this embodiment, the cation A in the general pyrochlore structure formula "A2B2O7" is a composite cation using lithium metal and lanthanide elements. This is believed to contribute to improving the ionic conductivity of the pyrochlore-type solid electrolyte.
[0079] Cation B is a metal cation different from Aa and Ab, and is selected from transition metals or elements of Groups 13 to 15. B forms an octahedron surrounded by six oxygen atoms in its crystal structure. As the transition metal represented by B, Group 4 or Group 5 transition metals can be used; more specifically, at least one of Nb, Ta, Ti, Zr, Hf, and V can be used. As a Group 13 element represented by B, Al, Ga, and In can be used; as a Group 14 element, Ge and Sn can be used; and as a Group 15 element, Sb and Bi can be used. In this embodiment, Nb or Ta is used as B.
[0080] Anion X is an anion capable of replacing O atoms constituting the pyrochlore structure. X has a different electronegativity and polarizability than O atoms. At least one of O, F, Cl, Br, I, S, OH, and P can be used as the anion represented by X. The composition ratio γ of X is in the range of 0 < γ ≤ 1, and at least a portion of the O atoms constituting the pyrochlore structure is replaced by X. In this embodiment, F can be used as X.
[0081] The pyrochlore-type solid electrolyte of this embodiment possesses a defect structure containing lattice defects in its crystallization by replacing a portion of the O atoms constituting the pyrochlore structure with anions having electronegativity and polarizability different from that of the O atoms. The pyrochlore-type solid electrolyte of this embodiment is considered to have improved ionic conductivity due to the inclusion of a defect structure within the pyrochlore structure.
[0082] In the pyrochlore-type solid electrolyte of this embodiment, a portion of Aa and Ab is missing as a defect structure. The typical composition of pyrochlore is "A₂B₂O₇", with a cation A composition ratio of 2. In contrast, in the pyrochlore-type solid electrolyte of this embodiment, the composition ratios of Aa and Ab are "2-α" and "(1+α) / 3", respectively, and 0.6 < α < 2.0. Therefore, the total composition ratio of Aa and Ab is less than 2. That is, in the crystal structure of the pyrochlore-type solid electrolyte of this embodiment, at least any portion of Aa and Ab is missing. Furthermore, the composition ratio corresponding to the missing portions of Aa and Ab is (2α-1) / 3.
[0083] In addition to deviations in composition ratios, defect structures can also be formed in the above composition formulas by making the sum of the valences of the cations composed of Aa, Ab, and B and the anions composed of O and X negative.
[0084] Furthermore, the pyrochlore-type solid electrolyte of this embodiment is a composite anionic compound containing multiple anions such as O and X in the pyrochlore structure. Since the anion represented by X exists in the BO6 coordination octahedral structure, the alkali metal of Aa can be located in the central part of the space surrounding the BO6 coordination octahedron, rather than close to it. Therefore, the pyrochlore-type solid electrolyte of this embodiment is considered to have high ion conductivity when used under an electric field such as a battery.
[0085] Furthermore, the α, β, and γ values in the above composition affect lattice defects and ionic conductivity, and therefore are preferably used within appropriate ranges. If the values of α, β, and γ are large, the defect concentration within the crystal lattice increases; however, if these values exceed a certain amount, the concentration of the alkali metal, represented by Aa, decreases, and the ionic conductivity decreases. Therefore, it is preferable to control α within the range of 0.6 < α < 2.0, β within the range of 0 < β ≤ 1, and γ within the range of 0 < γ ≤ 1.
[0086] As a pyrochlore-type solid electrolyte, Li can be used as an example 1.25 La 0.58 Nb₂O₆F(LLNOF), Li 1.25 La 0.58 Ta₂O₆F (LLTOF). LLNOF and LLTOF use Li as the cation Aa, La as the cation Ab, and F as the anion X, with α=0.75, β=1, and γ=1. LLNOF uses Nb as the cation B, and LLTOF uses Ta as the cation B.
[0087] The pyrochlore-type solid electrolyte of this embodiment can yield 1×10 -3 Ionic conductivity exceeding S / cm. In the pyrochlore-type solid electrolyte of this embodiment, significantly higher ionic conductivity can be obtained than other oxide-type solid electrolytes such as garnet-type oxides.
[0088] Next, use Figure 7 The flowchart illustrates the manufacturing method of the secondary battery 1 according to this first embodiment.
[0089] First, such as Figure 7 As shown, in S10, an active material slurry preparation process is performed. In this process, electrode active materials (positive electrode active material 13 and negative electrode active material 23) are dispersed in a solvent to prepare an active material slurry. The active material slurry prepared from the positive electrode active material 13 is used as the positive electrode material 12 of the outer peripheral portion 10b and the central portion 10c of the second positive electrode. The active material slurry prepared from the negative electrode active material 23 is used as the negative electrode material 22 of the outer peripheral portion 20b and the central portion 20c of the second negative electrode.
[0090] Next, in S11, a mixture slurry preparation process is performed, in which a mixture of electrode active materials 13 and 23 and inorganic solid electrolyte 70 is dispersed in a solvent to prepare a mixture slurry. The mixture slurry prepared from positive electrode active material 13 and inorganic solid electrolyte 70 is used as the positive electrode material 12 of the first positive electrode outer periphery 10a and the second positive electrode outer periphery 10b. The mixture slurry prepared from negative electrode active material 23 and inorganic solid electrolyte 70 is used as the negative electrode material 22 of the first negative electrode outer periphery 20a and the second negative electrode outer periphery 20b.
[0091] Next, in S12, a slurry coating process is performed, in which active material slurry and a mixed slurry are coated onto the positive electrode current collector 11 and the negative electrode current collector 21. In the positive electrode current collector 11, active material slurry is coated onto the portions corresponding to the outer periphery 10b and the center portion 10c of the second positive electrode, and a mixed slurry is coated onto the portions corresponding to the outer periphery 10a of the first positive electrode. In the negative electrode current collector 21, active material slurry is coated onto the portions corresponding to the outer periphery 20b and the center portion 20c of the second negative electrode, and a mixed slurry is coated onto the portions corresponding to the outer periphery 20a of the first negative electrode.
[0092] like Figure 8 As shown, the positive current collector 11 and the negative current collector 21 are sized to simultaneously fabricate multiple positive electrodes 10 and multiple negative electrodes 20. A paste corresponding to the desired number of positive electrodes 10 is applied to the positive current collector 11 at predetermined intervals. A paste corresponding to the desired number of negative electrodes 20 is applied to the negative current collector 21 at predetermined intervals.
[0093] Next, in S13, a drying process is performed, in which the slurry coated on the positive current collector 11 and the negative current collector 21 is dried.
[0094] Next, in S14, a punching process is performed, in which the positive current collector 11, which has multiple positive electrodes 10, is punched to divide the positive current collector 11 into multiple positive electrodes 10, and the negative current collector 21, which has multiple negative electrodes 20, is punched to divide the negative current collector 21 into multiple negative electrodes 20.
[0095] Next, in S15, a stacking process is performed, in which the separator 30 is bent into a fan shape, and the positive electrode 10 and the negative electrode 20 are alternately stacked through the separator 30 to form a stack 40.
[0096] Next, in S16, an outer casing insertion process is performed, in which the laminate 40 of the positive electrode 10, negative electrode 20, and separator 30 is inserted into the internal space of the outer casing 50. The outer casing 50 is in a joined state except for the portions of the two laminated films 51 and 52 that are inserted into the laminate 40.
[0097] Next, in S17, an electrolyte injection process is performed, in which an electrolyte constituent material, which is the raw material for the gel polymer electrolyte 60, is injected into the internal space of the outer casing 50. In S18, a vacuum sealing process is performed, in which the outer casing 50 is vacuum sealed.
[0098] Next, in S19, a gelation process is performed, in which the electrolyte constituent material encapsulated in the outer casing 50 is gelled. In the gelation process, the electrolyte constituent material is polymerized by heating to a specified temperature, thus gelling.
[0099] Finally, in S20, a performance test is conducted on the secondary battery 1 produced in the processes up to S19, and the secondary battery 1 is completed.
[0100] According to the first embodiment described above, in the positive electrode 10 of the laminated secondary battery 1, an inorganic solid electrolyte 70 is disposed on the outer periphery 10a of the first positive electrode, which is connected to the bend in the separator 30b. This improves the ionic conductivity of the outer periphery 10a of the first positive electrode, where the high viscosity of the gel polymer electrolyte 60 easily leads to increased resistance, and reduces the current density unevenness of the positive electrode 10. As a result, the output characteristics and cycle characteristics of the secondary battery 1 are improved.
[0101] Furthermore, in this first embodiment, in the negative electrode 20 of the laminated secondary battery 1, an inorganic solid electrolyte 70 is disposed on the outer periphery 20a of the first negative electrode, which is connected to the membrane bend 30b. This improves the ionic conductivity of the outer periphery 20a of the first negative electrode, where the high viscosity of the gel polymer electrolyte 60 easily leads to increased resistance, and reduces current density unevenness in the negative electrode 20. As a result, the output characteristics and cycle characteristics of the secondary battery 1 are improved.
[0102] Furthermore, according to this first embodiment, when using an oxide-based solid electrolyte as the inorganic solid electrolyte 70, compared to using a sulfide-based solid electrolyte as the inorganic solid electrolyte 70, local decomposition caused by the reaction between the inorganic solid electrolyte 70 and the gel polymer electrolyte 60 can be suppressed. Therefore, by using an oxide-based solid electrolyte as the inorganic solid electrolyte 70, the current density unevenness between the positive electrode 10 and the negative electrode 20 can be effectively suppressed.
[0103] Furthermore, according to this first embodiment, by using a pyrochlore-type solid electrolyte with high ionic conductivity as the inorganic solid electrolyte 70, the ionic conductivity of the outer periphery of the first positive electrode 10a and the outer periphery of the first negative electrode 20a can be improved, and the uneven current density between the positive electrode 10 and the negative electrode 20 can be effectively suppressed.
[0104] Furthermore, according to this first embodiment, by providing the inorganic solid electrolyte 70 at the positive electrode 10 where the interfacial resistance between the electrode and the electrolyte is prone to increase, the ionic conductivity of the positive electrode 10 can be improved, and the uneven current density of the positive electrode 10 can be effectively suppressed.
[0105] Furthermore, according to this first embodiment, by disposing the inorganic solid electrolyte 70 on both sides of the positive electrode 10 and the negative electrode 20, the ionic conductivity of the positive electrode 10 and the negative electrode 20 can be improved respectively, and the uneven current density can be suppressed.
[0106] Furthermore, according to this first embodiment, by making the content of inorganic solid electrolyte 70 in the positive electrode 10 greater than the content of inorganic solid electrolyte 70 in the negative electrode 20, the ionic conductivity of the positive electrode 10, which is prone to increased interfacial resistance between the electrode and the electrolyte, can be preferentially improved, and the uneven current density between the positive electrode 10 and the negative electrode 20 can be effectively suppressed.
[0107] (Second Implementation)
[0108] Next, the second embodiment of this disclosure will be described. Hereinafter, only the parts that differ from the first embodiment described above will be described. In this second embodiment, the structures of the positive electrode material 12 and the negative electrode material 22 differ from those in the first embodiment described above.
[0109] In this second embodiment, in the first positive electrode peripheral portion 10a and the second positive electrode peripheral portion 10b, the positive electrode material 12 includes a positive electrode active material 13 and an inorganic solid electrolyte 70. In the positive electrode central portion 10c, the positive electrode material 12 includes the positive electrode active material 13 but does not include the inorganic solid electrolyte 70.
[0110] Furthermore, in the outer periphery of the first negative electrode 20a and the outer periphery of the second negative electrode 20b, the negative electrode material 22 includes a negative electrode active material and an inorganic solid electrolyte 70. In the central portion of the negative electrode 20c, the negative electrode material 22 includes a negative electrode active material 23 but does not include the inorganic solid electrolyte 70.
[0111] The content of inorganic solid electrolyte 70 in the outer periphery of the first positive electrode 10a and the outer periphery of the second positive electrode 10b can be the same or different. Similarly, the content of solid electrolyte in the outer periphery of the first negative electrode 20a and the outer periphery of the second negative electrode 20b can be the same or different.
[0112] The content of inorganic solid electrolyte 70 in the positive electrode 10 is preferably greater in the outer periphery of the first positive electrode 10a than in the outer periphery of the second positive electrode 10b. Since the resistance of the outer periphery of the first positive electrode 10a is more likely to increase compared to the outer periphery of the second positive electrode 10b, increasing the content of inorganic solid electrolyte 70 in the outer periphery of the first positive electrode 10a can increase the ionic conductivity of the outer periphery of the first positive electrode 10a and more effectively reduce current density unevenness.
[0113] Similarly, the content of inorganic solid electrolyte 70 in the negative electrode 20 is preferably greater in the outer periphery of the first negative electrode 20a than in the outer periphery of the second negative electrode 20b. Since the resistance of the outer periphery of the first negative electrode 20a is more likely to increase compared to the outer periphery of the second negative electrode 20b, increasing the content of inorganic solid electrolyte 70 in the outer periphery of the first negative electrode 20a can increase the ionic conductivity of the outer periphery of the first negative electrode 20a and more effectively reduce current density unevenness.
[0114] In the second embodiment described above, in the laminated secondary battery 1, an inorganic solid electrolyte 70 is disposed on both sides of the outer periphery 10a and the outer periphery 10b of the first positive electrode. This improves the ionic conductivity of the outer peripheries 10a and 10b of the positive electrode, which are prone to increased resistance due to the high viscosity of the gel polymer electrolyte 60, and reduces the current density unevenness of the positive electrode 10. As a result, the output characteristics and cycle characteristics of the secondary battery 1 are improved.
[0115] Furthermore, in this second embodiment, in the laminated secondary battery 1, an inorganic solid electrolyte 70 is disposed on both sides of the outer periphery of the first negative electrode 20a and the outer periphery of the second negative electrode 20b. This improves the ionic conductivity of the outer peripheries 20a and 20b of the negative electrodes, which are prone to increased resistance due to the high viscosity of the gel polymer electrolyte 60, and reduces the current density unevenness of the negative electrode 20. As a result, the output characteristics and cycle characteristics of the secondary battery 1 are improved.
[0116] Furthermore, according to this second embodiment, by making the content of inorganic solid electrolyte 70 in the outer periphery 10a of the first positive electrode more than that in the outer periphery 10b of the second positive electrode, the ionic conductivity of the outer periphery 10a of the first positive electrode can be increased, and the current density unevenness of the positive electrode 10 can be reduced more effectively.
[0117] Furthermore, according to this second embodiment, by making the content of inorganic solid electrolyte 70 in the outer periphery of the first negative electrode 20a greater than that in the outer periphery of the second negative electrode 20b, the ionic conductivity of the outer periphery of the first negative electrode 20a can be increased, and the current density unevenness of the negative electrode 20 can be reduced more effectively.
[0118] (Third Implementation)
[0119] Next, a third embodiment of this disclosure will be described. Hereinafter, only the parts that differ from the embodiments described above will be described. In this third embodiment, the structures of the positive electrode material 12 and the negative electrode material 22 differ from those in the embodiments described above.
[0120] In this third embodiment, the positive electrode material 12 comprises a positive electrode active material 13 and an inorganic solid electrolyte 70 in the first positive electrode peripheral portion 10a, the second positive electrode peripheral portion 10b, and the positive electrode center portion 10c. That is, in this third embodiment, the inorganic solid electrolyte 70 is added to the entire positive electrode 10.
[0121] In this third embodiment, the negative electrode material 22 comprises a negative electrode active material 23 and an inorganic solid electrolyte 70 in the first negative electrode outer peripheral portion 20a, the second negative electrode outer peripheral portion 20b, and the negative electrode center portion 20c. That is, in this third embodiment, the inorganic solid electrolyte 70 is added to the entire negative electrode 20.
[0122] The content of inorganic solid electrolyte 70 in the outer periphery of the first positive electrode 10a, the outer periphery of the second positive electrode 10b, and the central part of the positive electrode 10c can be the same or different. Similarly, the content of solid electrolyte in the outer periphery of the first negative electrode 20a, the outer periphery of the second negative electrode 20b, and the central part of the negative electrode 20c can be the same or different.
[0123] The preferred content of the inorganic solid electrolyte 70 in the positive electrode 10 is in the order of the outer periphery 10a of the first positive electrode > the outer periphery 10b of the second positive electrode > the central portion 10c of the positive electrode. The resistance of the outer periphery 10a of the first positive electrode tends to be higher than that of the outer periphery 10b of the second positive electrode, and the resistance of the outer periphery 10b of the second positive electrode tends to be higher than that of the central portion 10c of the positive electrode. Therefore, by ensuring that the content of the inorganic solid electrolyte 70 in the positive electrode 10 is in the order of the outer periphery 10a of the first positive electrode > the outer periphery 10b of the second positive electrode > the central portion 10c of the positive electrode, the current density unevenness of the positive electrode 10 can be reduced more effectively.
[0124] The preferred content of inorganic solid electrolyte 70 in the negative electrode 20 is in the order of the outer periphery 20a of the first negative electrode > the outer periphery 20b of the second negative electrode > the center portion 20c of the negative electrode. The resistance of the outer periphery 20a of the first negative electrode tends to be higher than that of the outer periphery 20b of the second negative electrode, and the resistance of the outer periphery 20b of the second negative electrode tends to be higher than that of the center portion 20c of the negative electrode. Therefore, by making the content of inorganic solid electrolyte 70 in the negative electrode 20 in the order of the outer periphery 20a of the first negative electrode > the outer periphery 20b of the second negative electrode > the center portion 20c of the negative electrode, the current density unevenness of the negative electrode 20 can be reduced more effectively.
[0125] According to the third embodiment described above, in the laminated secondary battery 1, an inorganic solid electrolyte 70 is disposed in the outer peripheral portion 10a of the first positive electrode, the outer peripheral portion 10b of the second positive electrode, and the central portion 10c of the positive electrode. This improves the overall ionic conductivity of the positive electrode 10, thereby enhancing the output and cycle characteristics of the secondary battery 1.
[0126] Furthermore, according to this third embodiment, in the laminated secondary battery 1, an inorganic solid electrolyte 70 is disposed in the outer periphery 20a of the first negative electrode, the outer periphery 20b of the second negative electrode, and the center portion 20c of the negative electrode. This improves the overall ionic conductivity of the negative electrode 20, thereby enhancing the output and cycle characteristics of the secondary battery 1.
[0127] (Example)
[0128] Next, use Figure 9 The embodiments and comparative examples of this disclosure will be described. The regions in the positive electrode 10 or negative electrode 20 of Embodiments 1-9 and Comparative Examples 1-4 where the inorganic solid electrolyte 70 is disposed differ, or the type of inorganic solid electrolyte 70 is different. Figure 9 In the diagram, the output and loop characteristics are displayed as relative values when the value of Comparison Example 1 is set to 100%.
[0129] Figure 9 The output performance and cycle characteristics were measured using a charge / discharge device manufactured by Hokuto Electric Co., Ltd. Figure 9 The output characteristics were evaluated under the following conditions: the discharge time was measured under constant current and constant voltage charging at 0.2C to 4.3V at 25°C, followed by constant current discharge at 10C to 2.5V. Figure 9 The cycle characteristics were evaluated by the number of cycles in which the discharge capacity was less than 80% of the initial discharge capacity. One cycle was defined as a charge-discharge cycle in which the discharge capacity was discharged to 4.3V at 1.0C and then discharged to 2.5V at 7C.
[0130] exist Figure 9 In Examples 1-9 and Comparative Examples 1-4, LiNi was used. 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is used as the positive electrode active material 13, and graphite is used as the negative electrode active material 23. In addition, the gel polymer electrolyte 60 used in Examples 1 to 9 and Comparative Examples 1 to 4 contains a vinylidene fluoride copolymer as a polymer, LiPF6 as a lithium salt, and ethylene carbonate as a solvent.
[0131] In Examples 1-7, a sulfide-based solid electrolyte was used as the inorganic solid electrolyte 70. In Examples 1-7, a sulfide-based solid electrolyte, Li6PS5Cl, was used as the sulfide-based solid electrolyte. In Examples 1-9 and Comparative Examples 1-4, the inorganic solid electrolyte 70 was added at a content of 5% when preparing the slurry for the positive electrode material 12 or the negative electrode material 22.
[0132] In Examples 8 and 9, an oxide-based solid electrolyte was used as the inorganic solid electrolyte 70. In Example 8, a garnet-type solid electrolyte, namely Li7La3Zr2O, was used. 12 (LLZ) was used as an oxide-based solid electrolyte. In Example 9, a pyrochlore-type solid electrolyte, namely Li... 1.25 La 0.58 Nb₂O₆F (LLNOF) is an oxide-based solid electrolyte.
[0133] In Comparative Example 1, inorganic solid electrolyte 70 was not used. In Comparative Examples 2-4, a sulfide-based solid electrolyte, namely Li6PS5Cl, was used as the inorganic solid electrolyte 70.
[0134] exist Figure 9 In the "Addition of Inorganic Solid Electrolyte" section, the parts of the positive electrode 10 and negative electrode 20 that have inorganic solid electrolyte 70 are displayed as "Yes", while the parts that do not have inorganic solid electrolyte 70 are empty.
[0135] Example 1: An inorganic solid electrolyte 70 (sulfide) is disposed on the outer periphery 20a of the first negative electrode. Example 2: An inorganic solid electrolyte 70 (sulfide) is disposed on the outer periphery 20a of the first negative electrode and the outer periphery 20b of the second negative electrode. Example 3: An inorganic solid electrolyte 70 (sulfide) is disposed on the outer periphery 20a of the first negative electrode, the outer periphery 20b of the second negative electrode, and the center portion 20c of the negative electrode.
[0136] Example 4: An inorganic solid electrolyte 70 (sulfide) is disposed on the outer periphery 10a of the first positive electrode. Example 5: An inorganic solid electrolyte 70 (sulfide) is disposed on the outer periphery 10a of the first positive electrode and the outer periphery 10b of the second positive electrode. Example 6: An inorganic solid electrolyte 70 (sulfide) is disposed on the outer periphery 10a of the first positive electrode, the outer periphery 10b of the second positive electrode, and the central portion 10c of the positive electrode.
[0137] In Example 7, an inorganic solid electrolyte 70 (sulfide) is disposed on the outer periphery of the first positive electrode 10a, the outer periphery of the second positive electrode 10b, the outer periphery of the first negative electrode 20a, and the outer periphery of the second negative electrode 20b. In Examples 8 and 9, an inorganic solid electrolyte 70 (oxide) is disposed on the outer periphery of the first positive electrode 10a, the outer periphery of the second positive electrode 10b, the outer periphery of the first negative electrode 20a, and the outer periphery of the second negative electrode 20b.
[0138] Comparative Example 2: An inorganic solid electrolyte 70 (sulfide) is disposed at the center portion 20c of the negative electrode. Comparative Example 3: An inorganic solid electrolyte 70 (sulfide) is disposed at the center portion 10c of the positive electrode. Comparative Example 4: An inorganic solid electrolyte 70 (sulfide) is disposed at both the center portion 20c of the negative electrode and the center portion 10c of the positive electrode.
[0139] like Figure 9 As shown, in all of Examples 1 to 9, the output characteristics and loop characteristics exceed 100%.
[0140] In Example 1, by providing an inorganic solid electrolyte 70 on the outer periphery 20a of the first negative electrode, the output and cycle characteristics of the secondary battery 1 exceeded 100%, which is an improvement over Comparative Example 1. This is believed to be a result of a reduction in the ion transport resistance of the outer periphery 20a of the first negative electrode where the inorganic solid electrolyte 70 is provided and a reduction in the unevenness of the current density of the negative electrode 20.
[0141] In Example 2, by distributing the inorganic solid electrolyte 70 to the outer periphery of the first negative electrode 20a and the outer periphery of the second negative electrode 20b, the output characteristics and cycle characteristics of the secondary battery 1 are higher than those in Example 1. This is considered to be a result of the reduced ion transport resistance of the outer periphery of the first negative electrode 20a and the second negative electrode 20b, and the reduced current density unevenness of the negative electrode 20 compared to Example 1.
[0142] In Example 3, by distributing the inorganic solid electrolyte 70 to the outer periphery 20a of the first negative electrode, the outer periphery 20b of the second negative electrode, and the center portion 20c of the negative electrode, the output characteristics of the secondary battery 1 are higher than those in Example 2. This is considered to be a result of a reduction in the overall ion transport resistance of the negative electrode 20, thus improving the output characteristics of the secondary battery 1. On the other hand, in Example 3, the cycle characteristics of the secondary battery 1 are lower than those in Example 2. This is considered to be a result of a reduction in ion transport resistance throughout the negative electrode 20, and a lower degree of improvement in current density unevenness compared to Example 2.
[0143] In Example 4, by providing the inorganic solid electrolyte 70 to the outer periphery 10a of the first positive electrode, the output and cycle characteristics of the secondary battery 1 exceeded 100%, and the output and cycle characteristics of the secondary battery 1 were improved compared to Comparative Example 1. This is considered to be a result of the reduction in ion transport resistance of the outer periphery 10a of the first positive electrode where the inorganic solid electrolyte 70 is provided and the reduction in current density unevenness of the negative electrode 20.
[0144] In Example 5, by providing the inorganic solid electrolyte 70 on the outer periphery 10a and the outer periphery 10b of the first positive electrode, the output characteristics and cycle characteristics of the secondary battery 1 are higher than those in Example 4. This is considered to be a result of the reduced ion transport resistance of the outer periphery 10a and the outer periphery 10b of the first positive electrode and the reduced current density unevenness of the negative electrode 20 compared to Example 4.
[0145] In Example 6, by distributing the inorganic solid electrolyte 70 to the outer periphery 10a of the first positive electrode, the outer periphery 10b of the second positive electrode, and the center portion 10c of the positive electrode, the output characteristics of the secondary battery 1 are higher than those in Example 5. This is considered to be a result of a reduction in the overall ion transport resistance of the positive electrode 10, thus improving the output characteristics of the secondary battery 1. On the other hand, in Example 6, compared to Example 5, the cycle characteristics of the secondary battery 1 are lower. This is considered to be a result of a reduction in the overall ion transport resistance throughout the negative electrode 20, and a result of a lower degree of improvement in current density unevenness compared to Example 5.
[0146] In Example 7, an inorganic solid electrolyte 70 is disposed on the outer periphery of the first positive electrode 10a, the outer periphery of the second positive electrode 10b, the outer periphery of the first negative electrode 20a, and the outer periphery of the second negative electrode 20b. In Example 7, compared to Example 2, where the inorganic solid electrolyte 70 is disposed on the outer periphery of the first negative electrode 20a and the outer periphery of the second negative electrode 20b, the output characteristics and cycle characteristics are improved. Similarly, in Example 7, compared to Example 5, where the inorganic solid electrolyte 70 is disposed on the outer periphery of the first positive electrode 10a and the outer periphery of the second positive electrode 10b, the output characteristics and cycle characteristics are improved by disposing the inorganic solid electrolyte 70 on both the outer periphery of the positive electrode 10a and 10b and the outer periphery of the negative electrode 20a and 20b, compared to the cases where the inorganic solid electrolyte 70 is disposed only on the outer periphery of the positive electrode 10a and 10b or only on the outer periphery of the negative electrode 20a and 20b.
[0147] Here, embodiments having the same structure in the positive electrode 10 and negative electrode 20 are compared with each other. In Embodiment 4, where the inorganic solid electrolyte 70 is disposed in the positive electrode 10, the output characteristics and cycle characteristics of the secondary battery 1 are improved compared to Embodiment 1, where the inorganic solid electrolyte 70 is disposed in the negative electrode 20. Similarly, in Embodiment 5, where the inorganic solid electrolyte 70 is disposed in the positive electrode 10, the output characteristics and cycle characteristics of the secondary battery 1 are improved compared to Embodiment 2, where the inorganic solid electrolyte 70 is disposed in the negative electrode 20. Likewise, in Embodiment 6, where the inorganic solid electrolyte 70 is disposed in the positive electrode 10, the output characteristics and cycle characteristics of the secondary battery 1 are improved compared to Embodiment 3, where the inorganic solid electrolyte 70 is disposed in the negative electrode 20. This is believed to be because, since the interfacial resistance between the electrode and the electrolyte in the positive electrode 10 is larger than that in the case where the inorganic solid electrolyte 70 is disposed in the negative electrode, the improvement in current density uniformity is greater when the inorganic solid electrolyte 70 is disposed in the positive electrode 10.
[0148] Comparing Examples 7 and 8 and 9, which differ only in the type of inorganic solid electrolyte 70, the output and cycle characteristics of the secondary batteries 1 in Examples 8 and 9, which use oxide-based solid electrolytes, are improved compared to Example 7, which uses a sulfide-based solid electrolyte. This is believed to be because oxide-based solid electrolytes can suppress localized decomposition due to reaction with the gel polymer electrolyte 60, thus improving the effect of oxide-based solid electrolytes in improving current density uniformity.
[0149] Comparing Example 8 and Example 9, which differ only in the type of oxide-based solid electrolyte, the output and cycle characteristics of the secondary battery 1 in Example 9, which uses a pyrochlore-type solid electrolyte (LLNOF), are improved compared to Example 8, which uses a garnet-type solid electrolyte (LLZ). This is attributed to the improved effect of the pyrochlore-type solid electrolyte on reducing current density unevenness due to its high ionic conductivity.
[0150] The output characteristics of Comparative Examples 2-4 are 100%. This is considered to be because the resistance of the outer peripheries 20a and 20b of the negative electrode and the outer peripheries 10a and 10b of the positive electrode, where the inorganic solid electrolyte 70 is not provided, remains unchanged, and the output characteristics are not improved. Furthermore, in Comparative Examples 2-4, the cycle characteristics are below 100%. This is considered to be a result of the reduced resistance of the central negative electrode 20c and the central positive electrode 10c where the inorganic solid electrolyte 70 is provided, leading to increased current density unevenness and further deterioration of the central negative electrode 20c and the central positive electrode 10c. In particular, the decrease in cycle characteristics is greater in Comparative Example 4, where the inorganic solid electrolyte 70 is provided on both the central negative electrode 20c and the central positive electrode 10c.
[0151] (Other implementation methods)
[0152] This disclosure is not limited to the embodiments described above, and various modifications can be made without departing from the spirit of this disclosure. Furthermore, the methods disclosed in the above embodiments can be appropriately combined within feasible limits.
[0153] For example, in the above embodiments, an example of applying the active material composite particles of this disclosure to a lithium-ion battery where the conductive ion is lithium ion has been described, but it can also be applied to secondary batteries with different conductive ions. Specifically, the active material composite particles of this disclosure can be applied to potassium-ion batteries with potassium ion conductivity, sodium-ion batteries with sodium ion conductivity, and the like.
[0154] Furthermore, in the first embodiment described above, an example was given in which the inorganic solid electrolyte 70 is disposed on the outer periphery of the first positive electrode 10a and the outer periphery of the first negative electrode 20a, and the inorganic solid electrolyte 70 is not disposed on the outer periphery of the second positive electrode 10b and the outer periphery of the second negative electrode 20b. However, it is also possible to configure the inorganic solid electrolyte 70 to be disposed on the outer periphery of the first positive electrode 10a and the outer periphery of the first negative electrode 20a, and the inorganic solid electrolyte 70 is disposed on the outer periphery of the second positive electrode 10b and the outer periphery of the second negative electrode 20b.
[0155] Furthermore, in the above embodiments, examples of providing the inorganic solid electrolyte 70 on both the positive electrode 10 and the negative electrode 20 have been described, but it is also possible to provide the inorganic solid electrolyte 70 on at least one of the positive electrode 10 and the negative electrode 20. When the inorganic solid electrolyte 70 is provided on at least one of the positive electrode 10 and the negative electrode 20, it is preferable to provide the inorganic solid electrolyte 70 on the positive electrode 10, where the interface resistance between the electrode and the electrolyte is relatively high.
[0156] Furthermore, in the above embodiments, a structure in which a plurality of diaphragm bends 30b are formed in the folded diaphragm 30 has been described, but it is sufficient for at least one diaphragm bend 30b to be formed.
Claims
1. A secondary battery, characterized in that, The device comprises electrodes, a separator, a gel polymer electrolyte, and an outer casing, the outer casing housing the electrodes, the separator, and the gel polymer electrolyte. The electrode has a positive electrode containing a positive active material and a negative electrode containing a negative active material. The positive electrode and the negative electrode are alternately stacked with the membrane in between. The diaphragm has a first portion that holds at least one of the positive and negative electrodes, and a second portion that bends to connect the first portions of the stacked diaphragms to each other. The electrode has a curved outer peripheral portion, an opposite outer peripheral portion, and a central portion. The curved outer peripheral portion includes a curved end portion located opposite to the second portion of the diaphragm. The opposite outer peripheral portion includes an opposite end portion located away from the second portion. The central portion is sandwiched between the curved outer peripheral portion and the opposite outer peripheral portion. The outer periphery of the curved side of at least one of the positive and negative electrodes contains an inorganic solid electrolyte. In the outer peripheral portion of the curved side, the outer peripheral portion of the opposite side, and the central portion of at least one of the positive electrode and the negative electrode in the electrode, the inorganic solid electrolyte is present or absent, or the content of the inorganic solid electrolyte is different.
2. The secondary battery according to claim 1, characterized in that, The curved side outer periphery is a region that includes the curved side end and has a length of less than 1 / 3 of the length of the electrode in the direction connecting the curved side end and the opposite side end.
3. The secondary battery according to claim 1, characterized in that, The opposite outer periphery contains at least one of the positive electrode active material and the negative electrode active material, as well as the inorganic solid electrolyte.
4. The secondary battery according to claim 3, characterized in that, The opposite outer periphery is a region that includes the opposite end and has a length of less than 1 / 3 of the length of the electrode in the direction connecting the curved end and the opposite end.
5. The secondary battery according to claim 4, characterized in that, The amount of inorganic solid electrolyte contained in the outer periphery of the curved side and the outer periphery of the opposite side is in the order of the outer periphery of the curved side > the outer periphery of the opposite side.
6. The secondary battery according to claim 3, characterized in that, At least one of the positive electrode active material and the negative electrode active material, as well as the inorganic solid electrolyte, are added to the central part.
7. The secondary battery according to claim 6, characterized in that, The amount of inorganic solid electrolyte contained in each of the curved outer periphery, the opposite outer periphery, and the center portion is in the order of curved outer periphery > opposite outer periphery > center portion.
8. The secondary battery according to claim 1, characterized in that, The electrode containing the inorganic solid electrolyte on the outer periphery of the curved side is the positive electrode.
9. The secondary battery according to claim 1, characterized in that, The electrodes containing the inorganic solid electrolyte on the outer periphery of the curved side are the positive electrode and the negative electrode.
10. The secondary battery according to claim 9, characterized in that, The amount of inorganic solid electrolyte contained in the positive electrode and the negative electrode is in the order of positive electrode > negative electrode.
11. The secondary battery according to claim 1, characterized in that, The inorganic solid electrolyte is an oxide-based solid electrolyte.
12. The secondary battery according to claim 11, characterized in that, The oxide-based solid electrolyte is a pyrochlore-type solid electrolyte with a pyrochlore structure.
13. The secondary battery according to claim 12, characterized in that, The composition formula of the pyrochlore-type solid electrolyte is Aa 2-α Ab (1+α) / 3 B2O 7-β X γ Aa is an alkali metal, Ab contains at least a lanthanide element, B is a cation different from Aa and Ab, X is an anion capable of replacing the O atom constituting the pyrochlore-type solid electrolyte, and in the compositional formula, α is in the range of 0.6 < α < 2.0, β is in the range of 0 < β ≤ 1, γ is in the range of 0 < γ ≤ 1, and the pyrochlore-type solid electrolyte contains defect structures.
Citation Information
Patent Citations
Radiator with resin tank
JP1986059199A
Method of recovering magnetic powder from magnetic recording material
JP1987079241A
Gel electrolyte battery and preparation method thereof
CN117790886A
Electrode, secondary battery, battery pack, and vehicle
JP2020161467A